Paradoks Pertumbuhan Ekonomi di Kawasan Urban Residential: Analisis Kesenjangan PDRB Per Kapita Kota Bekasi - Asep Pipin Hanapi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The macroeconomic dynamics of capital city buffer zones often present an anomaly between aggregate growth and the equitable distribution of individual welfare. This study examines the post-pandemic economic performance of Bekasi City, where the Economic Growth Rate in 2025 reached 5.39%, surpassing the averages of West Java Province (5.32%) and the national level (5.11%). However, this impressive expansion is overshadowed by stagnation at the per capita Gross Regional Domestic Product (GRDP) level, which plateaued at around IDR 52.51 million, significantly lagging behind the provincial average of IDR 59.87 million. Employing a descriptive quantitative approach based on panel and time-series data (2019-2025), this study unravels the structural roots of this disparity. The analysis reveals that the per capita gap is predominantly triggered by the urban residential trap effect. The surge in commuter migration, which boosted the population to 2.64 million, acts as a cannibalizing factor against the mathematical income ratio. Furthermore, the dominance of capital-intensive sectors such as the Manufacturing Industry (32.48%) induces capital flight towards the core agglomeration pole in Jakarta. Despite the depressed per capita value, the sociological condition dominated by minimum-wage working classes surprisingly yields a positive impact on income equality, evidenced by Bekasi City's Gini Index (0.407), which is more inclusive than the provincial average (0.416). These findings provide policy implications on the necessity of reorienting economic success metrics from merely pursuing GRDP towards stabilizing inequality and strengthening the local MSME sector.